An Assessment of Avian Diversity and Conservation Status in Orchha Wildlife Sanctuary, Madhya Pradesh, India - Singh, Mahendra; Kachhawa, Yati; Choyal, Rajaram; Charan, P. D. (Indian Forester, 2024)
The present study was explored to assess the diversity and status of bird species within the Orchha Wildlife Sanctuary situated in the state of Madhya Pradesh, India. The aims of the study were to identify species of birds, present status of different birds and factors influencing their distribution. A series of field survey was conducted during July 2022 to June 2023 for present investigation. The results of the study depict that species belongs to Passeriformes order was dominant (28.95%) followed by category of Threatened species, Accipitridae (8.55%). According to the (IUCN) International Union for the Conservation of Nature, 144 species were in the Least Concern category, 3 species in Critically Endangered category, 1 species in endangered category, 2 species in Near Threatened category, and 1 species invulnerable category. The findings of this study provide valuable insights into the avian biodiversity and needs for conservation of the Orchha Wildlife Sanctuary.